Analysis of new anti-corrosion coating system. (November 2013) - Cooke, J.; Dodds, P.
Abstract : Curtiss Wright Surface Technologies has worked in conjunction with Swansea University to analyse a new form of anti-corrosion metal treatment. The work reported focused on understanding both the wet chemistry of the coating system, as well as the unique behaviour of the dry film. The results showed how the coating system effectively self heals, by migration of the encapsulated corrosion inhibitors. This self healing, in combination with the high strength chemical bonding to the substrate, leads to greater anti-corrosion performance compared to traditional E-Coat and Powder Coat systems.